Case Study of Evidence-Based Nursing Implementation: Beetroot Juice Therapy to Increase Hemoglobin Levels in Pregnant Women with Anemia - Resi, Resi Novia (Papua Medicine and Health Science, 2025)
Anemia in pregnant women is a condition in which the mother has a hemoglobin (Hb) level in her blood of less than 11 g/dL, resulting from the inability of red blood cell-forming tissues to produce enough cells to maintain Hb concentration at a normal level. This study aims to provide nursing care to pregnant women with anemia through the administration of beetroot juice therapy to increase hemoglobin levels at Harapan Bunda Hospital, Batam. The method employed in this study was a case study based on the stages of nursing care, including assessment, nursing diagnosis, intervention, implementation, and evaluation. The assessment was conducted using a head-to-toe approach. The nursing diagnosis identified was fatigue related to anemia. The intervention was designed based on criteria and expected outcomes by applying beetroot juice therapy as an Evidence-Based Nursing (EBN) practice. The implementation was carried out over a 7-day period, and evaluation was based on the SOAP format. The results showed that administering beetroot juice to third-trimester pregnant women increased hemoglobin levels from 7.2 g/dL to 11.2 g/dL. The outcome criteria included decreased complaints of fatigue, reduced lethargy, increased energy, reduced headaches, decreased cyanosis and anxiety, and improved appetite. Therefore, it can be concluded that beetroot juice intervention effectively increases hemoglobin levels in pregnant women with anemia. It is recommended that pregnant women with anemia consider beetroot juice as a non-pharmacological therapy to help improve Hb levels.